Curcumin-loaded graphene oxide flakes as an effective antibacterial system against methicillin-resistant Staphylococcus aureus. Issue 3 (6th June 2018) - Bugli, F.; Cacaci, M.; Palmieri, V.; Di Santo, R.; Torelli, R.; Ciasca, G.; Di Vito, M.; Vitali, A.; Conti, C.; Sanguinetti, M.; De Spirito, M.; Papi, M.
Abstract : Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for serious hospital infections worldwide and represents a global public health problem. Curcumin, the major constituent of turmeric, is effective against MRSA but only at cytotoxic concentrations or in combination with antibiotics. The major issue in curcumin-based therapies is the poor solubility of this hydrophobic compound and the cytotoxicity at high doses. In this paper, we describe the efficacy of a composite nanoparticle made of curcumin (CU) and graphene oxide (GO), hereafter GOCU, in MRSA infection treatment. GO is a nanomaterial with a large surface area and high drug-loading capacity. GO has also antibacterial properties due mainly to a mechanical cutting of the bacterial membranes. For this physical mechanism of action, microorganisms are unlikely to develop resistance against this nanomaterial. In this work, we report the capacity of GO to support and stabilize curcumin molecules in a water environment and we demonstrate the efficacy of GOCU against MRSA at a concentration below 2 µg ml −1 . Further, GOCU displays low toxicity on fibroblasts cells and avoids haemolysis of red blood cells. Our results indicate that GOCU is a promising nanomaterial against antibiotic-resistant MRSA.